Primary porocarcinoma of the nipple with metastasis: A case report of a rare entity with molecular analysis and imaging correlation - Alireza Salem; Hannah L. Chung; Lavinia P. Middleton (Elsevier, 2023)
Porocarcinoma (PC) is a rare malignant skin adnexal tumor, accounting for approximately 0.005% to 0.02% of all malignant cutaneous neoplasms. It occurs most commonly in the sun-exposed extremities. To our knowledge, only one case of a primary nipple eccrine poroma (benign counterpart of PC) has been reported in the literature. Herein we report a patient with a primary PC of the left nipple with metastasis to the left axilla.